FINANCING INNOVATIVE-STRATEGIC DEVELOPMENT OF ENTERPRISES IN THE CONTEXT OF THE EXPERIENCE ECONOMY - Olesia Iastremska; Olha Bielienkova; Oksana Bondar-Pidhurska; Volodymyr Skakun; Vira Ruban; Sviatoslav Khimich (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article explores the peculiarities of financing innovative and strategic development of enterprises in the context of the experience economy, which takes into account the necessity of creating a unique customer experience and emotional value. The study reveals the characteristics of implementing innovative and strategic projects within the framework of the experience economy, emphasizing the role of emotional aspects in consumer behaviour. The authors analyze the main features of the strategy for managing the innovative development of enterprises (completion of the strategy development process, enhancing feedback, uncertainty). It is concluded that the successful implementation of innovation management strategies in the context of financing requires enterprises to be willing to adapt to changes and address tasks related to innovations. Flexibility and responsiveness to internal and external factors are key to effective competition and supporting sustainable development in a volatile market. The authors conducted an analysis of investment projects in Ukraine by sectors (energy, transport and logistics, agro sector, green metallurgy, critical materials, housing construction, reconstruction and building materials, pharmaceuticals and medical sector, ICT and digital sector) and assessed the impact of experience economy tools. It has been established that the energy sector has the greatest potential for attracting investments, given the large volume of financing (USD 79.8 billion) and innovative experience economy tools such as ecological marketing. This approach promotes the attraction of "green" investments and enhances investor confidence. It is recommended that when developing a strategy for financing innovative and strategic development, the number and complexity of innovative projects planned for simultaneous implementation in the market should be taken into account. This influences the determination of the volume of financial, human, and technological resources required for the successful implementation of innovations. A balanced approach to resource allocation and risk management will help achieve sustainable growth for enterprises, which is particularly important in the face of ever-increasing consumer expectations in the experience economy.